SnO2 Physical and Chemical Properties due to the impurity doping - Rivera Escobar, R. (2013)
AbstractFirst-principles calculations based on the Density Functional Theory (DFT) within the generalized gradient approximation (GGA), and the introduction of intra-atomic interaction term for strongly correlated electrons (DFT+U), have been utilized to study defective SnO2 crystals. Introduction of some impurities, such as F, Ga, Al and Cr affect the structural, electronic and magnetic properties of tin dioxide. F doping produces alterations in the structure, with Sn atoms moving away from the impurity and O atoms moving closer to it; and, the system presents n-type electrical conductivity. Ga impurity incorporation distorts its surrounding, with the atoms moving closer to the impurity whereas the electrical properties of crystal remain unchanged. Results for Al impurity are almost the same as those for the Ga-doping. Cr-doping produces the atoms in the neighbourhood of the point defect to move towards it, the band gap has been slightly reduced and we observe the occurrence of a local magnetic moment. Index TermsSnO2, Impurity doping, DFT, point defects.